Changes on the take-off phase of the 400 meters hurdles clearance induced by the use of the non-dominant leg as the lead leg - Valamatos, M.-J.; Valamatos, M.-Jo.; Veloso, A.; Santos, P. M.-H. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction The support phase of the hurdles take-off is accomplished by a stretching shortening cycle muscle action which requires a high level of power output and muscle stiffness. The 400 m hurdles expert is an athlete able to perform the hurdles clearance using both legs as a lead leg. To maintain the best performance during the entire running, the muscle-tendon complexes of both legs should have a similar behaviour, in order to maintain the running sequence and the horizontal velocity (Mero & Luhtanen, 1984). The purpose of this study was to investigate changes on the mechanical power output variables produced by the muscle-skeletal system on the take-off phase of hurdles clearance, when using the non-dominant leg as a lead leg. Methods Seven national elite male athletes (body mass 71.79 ± 5.84 Kg; height 1.82 ± 0.06 m; age 24.43 ± 5.68 years old; 400 mH best 51.55 ± 1.72 s) participated in this study. The performance of the clearance action was high-speed video recorded at 250 Hz (Redlake PCI 1000), and 2D coordinates of the athlete body joints were obtained. Joint linear and angular displacement and velocity parameters as well as total body centre of mass (BCM) kinematics were calculated. The regression equations adapted by Jacobs et al., (1996) were used to estimate the length changes of the muscle tendon complex during the contact phase of the take-off of the clearance action. A three axial force platform was installed on the track, and the ground reaction forces (Fz, Fy and Fx) were recorded synchronized with video data. These procedures were repeated for the dominant and non-dominant leg. The differences between both conditions were tested using T-Tests for paired samples. When the athletes use the non-dominant leg, there was an increase of the total contact time (11.5%), due to a significant increase of both breaking (13.6%) and propulsive (8.1%) contact times. This increase of breaking contact time associated to an excessive breaking force, originated a substantial reduction of the horizontal velocity of the BCM (11.1%). The muscle length changes were similar in both conditions, pointed out that this muscle action was a stretching shorting cycle. However, the extensor muscles of the non-dominant leg showed less capability to produce mechanical power during the shortening phase, because they required more time to produce similar horizontal propulsive force, and an increase of the stretching phase. These results allow us to conclude that the differences on the mechanical output between the two legs are marked important. In order to improve the overall performance of the hurdler, great attention should be placed to include on the training routines specific clearance exercises for both legs.